Levas Vladimirovas and the Peripeteia of the Book Return of the Old Vilnius University Library - Kažuro, Ina; Grigonis, Evaldas (Bibliotheca Lituana, 2014)
The authors make an attempt to elucidate and summarize activity of Levas Vladimirovas as Director of Vilnius University Library (further on referred to as VUL ) in 1956–1959 returning to Vilnius books which belonged to the old VUL as well as other institutions connected with the old Vilnius University and which were taken out in the first half of the 19th c. to Russia. L. Vladimirovas managed to get the books back from the fourlibraries of Soviet Union in Moscow, Leningrad (present-day Saint Petersburg), Kiev and Kharkiv, though in the 19th c. and in the beginning of 20th the books were allotted to yet more educational and scholarly institutions of the Russian Empire (such as Tartu and Kazan Universities, etc.). There has been an investigation carried out of two collections of the Rare Book Department (i.e., books of the restored old VUL – Bibliotheca Academiae Vilnensis – and collection of Old Slavic books) in the years 2011–2012 and an exact number of returned books was estimated. The article presents the results of this investigation.
Keywords: none